Prognostic role of the Donor Risk Index, the Eurotransplant Donor Risk Index, and the Balance of Risk score on graft loss after liver transplantation - Lozanovski, Vladimir J.; Probst, Pascal; Arefidoust, Alireza; Ramouz, Ali; Aminizadeh, Ehsan; Nikdad, Mohammadsadegh; Khajeh, Elias; Ghamarnejad, Omid; Shafiei, Saeed; Ali-Hasan-Al-Saegh, Sadeq; Seide, Svenja; Kalkum, Eva; et al. (Transplant international, 2021)
This study aimed to identify cutoff values for donor risk index (DRI), Eurotransplant (ET)-DRI, and balance of risk (BAR) scores that predict the risk of liver graft loss.